Werner's syndrome: A case report and review of literature - Farhana Tahseen Taj; Divya Vupperla; Sridevi Raichur; Jolika Ardeshana (Our Dermatology Online, 2018)
Werner's Syndrome also known as Pangeria is an autosomal recessive disorder characterized by premature aging, increased risk of malignancies and atherosclerosis. The Global incidence rate is less than 1 in 100,000 live births. The incidence is higher in Japan and Sardinia affecting 1 in 20,000 - 40,000 live births and 1 in 50,000 live births respectively. Individuals with this disorder typically grow and develop normally until they reach puberty. Affected individual usually do not have a growth spurt, resulting in short stature. The characteristic aged appearance typically begins to develop when they are in their twenties and includes graying and loss of hair, a hoarse voice, and thin, hardened skin. They may also have a facial appearance described as "bird-like facies." Werner's Syndrome has been described as "Caricature of ageing" by Epstein et al. 1996. An OMIM number # has been assigned to Werner's Syndrome with phenotype MIM number 277700 (OMIM#277700).